HOMESCHOOLING: AN ALTERNATIVE TO NEW NORMAL ADAPTATION OF LEARNING - Eka Damayanti; Eva Meizara Puspita Dewi; Novita Maulidya Jalal; Nurfajriyanti Rasyid; Nurhaerani Haeba (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:This research aims at finding out the public perception about the homeschooling which is chosen as an alternative in adaptation to the new normal learning. This research took forty-eight participants who are dominated by educators and magister or profession. Questionnaire as the instrument on this research was shared via google form. The collected data were analyzed by using descriptive statistics. The findings show that the participants think about the theme "Homeschooling: An Alternative to New Normal Adaptation of Learning" in workshop activities suitable with the conditions of the covid-19 pandemic and fulfill the participants’ needs. The previous studies show that many things should be considered by looking at the advantages and risks of applying homeschooling, which means that other alternatives such as pleasant activities can be applied during the new normal.Abstrak:Penelitian ini bertujuan untuk mengetahui persepsi masyarakat tentang homeschooling yang dipilih sebagai alternatif dalam adaptasi terhadap pembelajaran normal baru. Penelitian ini mengambil empat puluh delapan partisipan yang didominasi oleh tenaga pendidik dan magister atau profesi. Angket sebagai instrumen dalam penelitian ini dibagikan melalui formulir google. Data yang terkumpul dianalisis dengan menggunakan statistik deskriptif. Temuan menunjukkan bahwa peserta memikirkan tema "Homeschooling: Sebuah Alternatif Pembelajaran Adaptasi Normal Baru" dalam kegiatan lokakarya yang sesuai dengan kondisi pandemi Covid-19 dan memenuhi kebutuhan peserta. Studi sebelumnya menunjukkan bahwa banyak hal yang harus diperhatikan dengan melihat keuntungan dan risiko penerapan homeschooling, yang artinya alternatif lain seperti aktivitas menyenangkan dapat diterapkan pada saat baru normal.